2019
DOI: 10.1016/j.celrep.2019.02.058
|View full text |Cite
|
Sign up to set email alerts
|

Functional Interaction between U1snRNP and Sam68 Insures Proper 3′ End Pre-mRNA Processing during Germ Cell Differentiation

Abstract: Highlights d Sam68 controls an extensive splicing program across meiosis in male germ cells d Sam68 prevents selection of premature alternative last exons d Proximity of Sam68 and U1snRNP motifs identifies Sam68 target last exons d Sam68 cooperates with U1snRNP in preventing premature transcript termination

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 46 publications
5
41
0
Order By: Relevance
“…This study focused on the neuronal isoform selection in 3′ UTR by SAM68 and demonstrated their functional aspects through the identification of a novel target IL1RAP in neurons (Figure 5). Very recently, two articles also elucidated the interaction between SAM68 and U1 small nuclear ribonucleoprotein particle (snRNP) as a global mechanism underlying ALE regulation by SAM68 (Naro et al., 2019, Subramania et al., 2019), supporting our findings in the CNS. U1 snRNP prevents premature transcript termination by inhibition of cryptic PASs (Berg et al., 2012, Kaida et al., 2010).…”
Section: Discussionsupporting
confidence: 85%
“…This study focused on the neuronal isoform selection in 3′ UTR by SAM68 and demonstrated their functional aspects through the identification of a novel target IL1RAP in neurons (Figure 5). Very recently, two articles also elucidated the interaction between SAM68 and U1 small nuclear ribonucleoprotein particle (snRNP) as a global mechanism underlying ALE regulation by SAM68 (Naro et al., 2019, Subramania et al., 2019), supporting our findings in the CNS. U1 snRNP prevents premature transcript termination by inhibition of cryptic PASs (Berg et al., 2012, Kaida et al., 2010).…”
Section: Discussionsupporting
confidence: 85%
“…Sam68 promotes exon 2 inclusion ( Fig. 2d, e) and it cooperates with the spliceosomal U1snRNP in exon recognition 28,22 . Analysis of testes from juvenile Sam68 knockout mice (P10) showed a significant reduction in Spo11 exon 2 inclusion (Fig.…”
Section: A Reduced Rnapii Elongation Rate Promotes Splicing Of Spo11αmentioning
confidence: 93%
“…Notably, ZFC3H1, which is specific to PAXT (Meola et al, 2016), was as abundant as the NEXT adaptor ZCCHC8 in Biotin-U1 AMO XLPD-MS (Table S4). Sam68/KHDRBS1 has been recently shown to bind in proximity to U1 and play a role in 3 0 end processing in germ cells (Naro et al, 2019). Thus, U1-CPAFs at the first 5 0 ss plays a crucial role in telescripting in genes with long first introns.…”
Section: U1 Amo Activates U1-cpafs Without Releasing U1mentioning
confidence: 99%